IMPLEMENTASI CORPORATE SOSIAL RESPONSIBILITY (CSR) PADA PT. CHEVRON PACIFIC INDONESIA (PT. CPI) DI PROVINSI RIAU - , ANNE MIDNITASARI; , Dr. Paripurna P Sugarda, S.H., M.Hum., LL.M. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aims of this research are to find out how far the Implementation of the run PT Chevron Pacific Indonesia rules (PT. CPI) contained in Article 74 of Law No. 40 year 2007 on Limited Liability Company. in Article 74 pharagraph (4) set of social and environmental responsibility, and then in 2012 published regulations implementing Article 74 of the Government Regulation No. 47 year 2012 on Social and Environmental Responsibility Company Limited. PT CPI as one of Indonesiaâs largest oil and gas companies and contractors alike as a special unit of executing upstream oil and gas became the target of research. The formulation of the problem is how CSR management in Indonesia, especially after the publication of Law No. 40 year 2007 on Limited Liability Companies (UUPT) Article 74 governing social and environmental Responsibilities and how the adoption of social and environmental responsibility at PT. CPI in Riau Province. The method used is the juridical approach in empirical, study and analyse the problems that s et legally by looking at the empirical facts objectively. The data have been obtained from the results from the library research and field research were analyzed qualitatively hereinafter are written in a descriptive. The result showed that the implementation of CSR be compulsory and should be accounted for by law since the enactment of the UUPT. The Implementation of CSR is valid for any company that move in the fields of natural resources or related to natural resources. So it is with TNC must submit to the prevailing law in Indonesia. PT. CPI who has been standing for more than half a century has implemented CSR because principled besides on ethics code of conduct business. PT. CPI also apply âThe Chevron Wayâ, namely the growing together of employees, partnership and its performance, reach a maximun result through the right ways and uphold values integrity, trust, diversity, breakthrough, protecting human and environment and high performance. PT. CPI has a special department for implementing CSR is routinely named the PGPA (Policy, Government and Public Affairs) liaison between companies, government and society.